2020
DOI: 10.1155/2020/8503047
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐Analysis of Randomized Controlled Trials of the Effects of Tai Chi on Blood Pressure

Abstract: Objectives. The purpose of this study was to investigate the influences of Tai Chi on blood pressure (BP) using the meta-analysis. Methods. This paper used 6 e-resource databases, and randomized controlled trials on the role of Tai Chi on blood pressure were retrieved. Besides, the meta-analysis was conducted according to the guidelines of the Moose-recommendations and applied with Review Manager 5.3, and the risk of bias assessment was performed with the Cochrane Collaboration’s tool. The inclusion, data extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…From the 210 SRs of Tai Chi, 47 SRs [ 60 106 ] were selected for the final evidence synthesis and 114 estimates of effect, representing 59,306 adult participants in RCTs, were extracted from 37 SRs [ 61 , 62 , 64 , 66 – 68 , 70 , 71 , 73 75 , 77 , 79 – 88 , 90 94 , 96 98 , 100 – 106 ]. Estimates of effects were not extracted, and the GRADE certainty of the evidence was not appraised for four SRs with unreliable meta-analyses [ 65 , 76 , 78 , 99 ] and six SRs with no meta-analysis [ 60 , 63 , 69 , 72 , 89 , 95 ]. No results were extracted from, nor was the AMSTAR-2 quality formally appraised or reported for 163 SRs (164 articles) because for 79 SRs, a far more recent SR, typically with more primary studies, was identified; for 46 SRs (47 articles) following further consideration, a SR of higher quality and/or with more primary studies in the meta-analysis for the PCO was selected; and for 38 of the SRs that did not conduct a meta-analysis, the PCO were reported by a SR with a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the 210 SRs of Tai Chi, 47 SRs [ 60 106 ] were selected for the final evidence synthesis and 114 estimates of effect, representing 59,306 adult participants in RCTs, were extracted from 37 SRs [ 61 , 62 , 64 , 66 – 68 , 70 , 71 , 73 75 , 77 , 79 – 88 , 90 94 , 96 98 , 100 – 106 ]. Estimates of effects were not extracted, and the GRADE certainty of the evidence was not appraised for four SRs with unreliable meta-analyses [ 65 , 76 , 78 , 99 ] and six SRs with no meta-analysis [ 60 , 63 , 69 , 72 , 89 , 95 ]. No results were extracted from, nor was the AMSTAR-2 quality formally appraised or reported for 163 SRs (164 articles) because for 79 SRs, a far more recent SR, typically with more primary studies, was identified; for 46 SRs (47 articles) following further consideration, a SR of higher quality and/or with more primary studies in the meta-analysis for the PCO was selected; and for 38 of the SRs that did not conduct a meta-analysis, the PCO were reported by a SR with a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…24 RCTs (Eng.) Gov Meta-analysis Critically low Dong 2020 [ 65 ] Adults, older adults ( n = 1608) with or without hypertension Systolic and diastolic BP 30–120 min 1–7 times/week, 8–24 weeks TC vs noRx, Ex Jan 2019 6 databases (Eng. Chin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the 210 SRs of Tai Chi, 47 SRs were selected for the nal evidence synthesis and 114 estimates of effect, representing 59,306 adult participants in randomised controlled trials, were extracted from 37 SRs. Estimates of effects were not extracted and the GRADE-certainty of the evidence was not appraised for four SRs with unreliable meta-analyses [64,75,77,98] and six SRs with no meta-analysis [59,62,68,71,88,94]. No results were extracted from, nor was the AMSTAR-2 quality formally appraised or reported for 163 SRs (164 articles) because for 79 SRs a far more recent SR, typically with more primary studies was identi ed; for 46 SRs (47 articles) following further consideration, a SR of higher quality and/or with more primary studies in the meta-analysis for the PCO was selected; and for 38 of the SRs that did not conduct a meta-analysis, the PCO were reported by a SR with a meta-analysis (Additional le 4).…”
Section: Study Selection For Evidence Synthesismentioning
confidence: 99%
“…Clinically important reductions in both systolic and diastolic blood pressure were found for people with essential hypertension (moderate to low certainty) [101] and diabetes mellitus (moderate certainty) [105]. There was probably no effect for normotensive adults, however, the estimates are not reported because some RCTs were excluded from the nal the meta-analyses and no sensitivity analysis was reported [64]. The antihypertensive effects for people with essential hypertension were greatest when Tai Chi was compared to no intervention or health education (moderate to low certainty, large effect), followed by anti-hypertensive medication (low certainty, moderate effect), and then other exercise interventions (moderate to low certainty, small effect) [101].…”
Section: Cardiovascular Diseases Diabetes and Risk Factorsmentioning
confidence: 99%